Optimasi Antena Mikrostrip 915 MHz Substrat Jeans Patch Slot Persegi Menggunakan CST Studio - M. Iqbal; Sopian Soim; Martinus Mujur Rose (Bulletin of Computer Science Research, 2023)
Microstrip antennas using jeans substrates have advantages in ease of manufacture, flexibility of use because they are flexible and fashionable, and are very suitable for application in telemedicine devices with the application of Industrial, Scientific and Medical or ISM frequency bands. In this study, the use of a microstrip antenna with a textile substrate was designed with CST studio simulation software to obtain antenna performance according to the expected working frequency, namely at a frequency of 915Mhz. From the results of the initial calculations and design, the patch size obtained is 172,817mm for the patch width value and 126,7476mm for the patch length value. In testing the vswr value, the vswr value is at a value of 14 before optimization and 1.2 after optimization. In testing the S parameter value, it produces a reading of -23 after optimizing the initial value of -3.7 db. The impedance value recorded is 50ohm from the previous value of 47.4ohm so that it is in accordance with the output impedance characteristics originating from Loa915 mhz.